Pengembangan Media Magic Box Sikla (Siklus Air) pada Pembelajaran IPA Materi Siklus Air Kelas V - Robiatul Adawiyah; Aiman Faiz; Dewi Yuningsih (Universitas Muhammadiyah Enrekang, 2022)
This study aims to develop three-dimensional concrete media in science learning class V and to determine the feasibility of the Magic Box Sikla media product (Water cycle) using the Borg and Gall model of research and development (R&D) modified by Sugiyono. In order to help overcome the problems found in the classroom in learning science in elementary school. The developed product can be known for its serviceability through media validation, material validation and product testing. The subjects in this study were fifth grade students of SDIT Hudzaifah Ibnu Yaman. The data collection instrument used in this study was a Likert scale questionnaire with quantitative descriptive data analysis and percentages. The results of this study are in the form of three-dimensional concrete media, namely Magic Box Sikla (Water Cycle) in science learning grade V. The results of the feasibility test of Magic Box Sikla (Water Cycle) learning media according to material experts obtained a final score of 93.63% with a very feasible category. According to media experts, it obtained a final score of 93% with a very decent category, then in a limited trial it got a score of 84.94% with a very decent category, so it can be concluded that the Magic Box Sikla (water cycle) media is suitable for use as a medium in science learning.